Evaluation of Minimum Service Standards (SPM) of Education Administration : (A Study on MTSN Batang) - Maskur Maskur; Indra Kertati; Charis Christiani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the implementation of the Minimum Service Standards (SPM) for education administration in MTsN Batang, identify supporting and inhibiting factors, and formulate recommendations for service improvement. The study used a mixed-methods design with an evaluative approach to the CIPP model. Quantitative data were collected through questionnaires from 60 respondents, while qualitative data were collected through in-depth interviews and observations. Quantitative data were analyzed using descriptive statistics and Kruskal-Wallis tests, while qualitative data were analyzed using Miles and Huberman's thematic analysis. The study found that SPM implementation reached 72%, with the highest achievement in student administration (85%) and the lowest in financial administration (58%). The Kruskal-Wallis test showed a significant difference in perception between groups (p=0.032). The thematic analysis identified three themes: digitization of services, human resource capacity, and transparency of accountability. The implications of the research show the need to increase human resource capacity, optimize management information systems, and strengthen coordination with the Ministry of Religion.